Actin Crosslinking Family Protein 7 Deficiency Does Not Impair Hearing in Young Mice - Gilbert, Benjamin L.; Zhu, Shaoyuan; Salameh, Ahlam; Sun, Shenyu; Alagramam, Kumar N.; McDermott, Brian M. (Frontiers in Cell and Developmental Biology, 2021)
To enable hearing, the sensory hair cell contains specialized subcellular structures at its apical region, including the actin-rich cuticular plate and circumferential band. ACF7 (actin crosslinking family protein 7), encoded by the gene Macf1 (microtubule and actin crosslinking factor 1), is a large cytoskeletal crosslinking protein that interacts with microtubules and filamentous actin to shape cells. ACF7 localizes to the cuticular plate and the circumferential band in the hair cells of vertebrates. The compelling expression pattern of ACF7 in hair cells, combined with conserved roles of this protein in the cytoskeleton of various cell types in invertebrates and vertebrates, led to the hypothesis that ACF7 performs a key function in the subcellular architecture of hair cells. To test the hypothesis, we conditionally target Macf1 in the inner ears of mice. Surprisingly, our data show that in young, but mature, conditional knockout mice, cochlear hair cell survival, planar cell polarity, organization of the hair cells within the organ of Corti, and capacity to hear were not significantly impacted. Overall, these results fail to support the hypothesis that ACF7 is an essential hair cell protein in young mice, and the purpose of ACF7 expression in the hair cell remains to be understood.